The solar charging backpack - Hafizul Azwa, Nurul Aliya; Saiful Nizam, Umar Uzair; Mohd Rusna, Mohamad Syazwan Hakim; Abdullah Sani, Muhammad Danial Aiman; Mohammad, Noorita (Universiti Teknologi MARA, Negeri Sembilan, 2025)
All undergraduate business students in the Marketing program (BA270) at Universiti Teknologi MARA (UiTM) must undertake the subject Innovation and New Product Planning (MKT523). Students, trekkers, and people in off-grid locations increasingly require renewable energy sources as they rely more on portable electronic gadgets such as smartphones and tablets. Traditional charging methods are ineffective in such areas due to the lack of reliable electricity sources. We recommend the Solar Backpack as a revolutionary, multicomponent solution that offers clean, portable energy while promoting sustainable living practices. The Solar Backpack features thin, foldable solar panels that harvest solar power and convert it into electric energy, which is stored in an onboard rechargeable battery. Built-in USB ports allow users to recharge their electronic devices, while LED indicators display power status during charging. The backpack is made from recycled, durable materials to create a waterproof product suitable for outdoor activities and environments. The Solar Backpack includes all the necessary features to serve as an outstanding choice for individuals who care about the environment and require mobile power and portable storage. The Solar Backpack represents modern green technology advancement through its ability to replace traditional energy sources with renewable power. Both functionally and environmentally beneficial, it is a product well worth investing in to promote sustainable innovation.